Economic Performance, Voting, and Political Support: A Unified Approach - Chappell, Henry W. (The Review of Economics and Statistics, 1990)
A presidential vote function and a presidential approval ratings function are jointly estimated for U.S. post-war observations. The estimation technique treats the two equations as seemingly unrelated regressions with unequal numbers of observations. Cross-equation restrictions implying that voters and poll respondents use identical standards in judging the economic performance of incumbents are imposed and tested. Estimates show that both votes and approval ratings are influenced by GNP growth and inflation. The results suggest that poll respondents are more inflation averse than voters; however, tests of this hypothesis are not conclusive.